Strengthening of preloaded RC beams using prestressed carbon textile reinforced mortar plates. (April 2021) - Du, Y.X.; Shao, X.; Chu, S.H.; Zhou, F.; Su, R.K.L.
Abstract: Carbon textile reinforced mortar (CTRM) is an advanced composite material that has excellent fire resistance, high strength and ductility, and good energy dissipation ability. Nevertheless, its full potential has not been fully investigated in the literature. In this paper, the flexural behaviour of preloaded reinforced concrete (RC) beams strengthened with a prestressed CTRM plate is explored. RC beams with and without an attached CTRM plate under various preloading conditions are tested. Their load-deflection and load-strain properties, bending capacity, ductility, and crack pattern and width are subsequently examined. The test results show that the prestressed CTRM plates can effectively inhibit the propagation of cracking and significantly increase the cracking and ultimate loads. The findings from this study are useful in advancing the use of CTRM to repair, retrofit and strengthen existing RC structures.